Polydopamine-functionalized black phosphorus quantum dots for cancer theranostics. (June 2019) - Li, Zhongjun; Xu, Han; Shao, Jundong; Jiang, Chao; Zhang, Feng; Lin, Jing; Zhang, Han; Li, Jianqing; Huang, Peng
Graphical abstract: The rapid degradation of black phosphorus (BP) with oxygen and moisture causes the innate instability that is the Achilles' heel of BP, a facile surface passivation strategy is developed to prepare polydopamine coated BP quantum dots (denoted as BP@PDA) with excellent stability and high photothermal conversion efficiency for cancer theranostics. Abstract: Black phosphorus (BP) is a promising theranostic agent owing to its excellent photothermal property, biocompatibility and biodegradability. However, the rapid degradation of BP with oxygen and moisture causes the innate instability that is the Achilles' heel of BP, hindering its further applications in cancer theranostics. Herein, a facile surface passivation strategy was developed to prepare polydopamine (PDA) coated BP quantum dots (QDs) (denoted as BP@PDA) through self-polymerization method. PDA with enriched phenol groups plays as a scavenger of reactive oxygen, which can efficiently prevent the oxidation of BP quantum dots and make them much stable in water (∼90% for BP@PDA vs. only 10% for pure BP QDs after 10 days storage). Furthermore, PDA with strong near-infrared (NIR) absorption could greatly improve the photothermal conversion efficiency (PCE) of BP QDs from 22.6% to 64.2% (∼2.84-fold higher). Considering the excellent biodegradability and good biocompability of both BP QDs and PDA, the as-prepared BP@PDA hold great potential for cancer theranostics.